Pakikipagkapwa Pilipinong lapit sa pananaliksik : pamumuno, pagsasakapangyarihan, pagkamamamayan, pananagutang panlipunan at pakikipamayapa - Javier, Roberto Estrada Jr. (Quezon City, Philippines Central Book Supply, Inc.for De La Salle University, 2012)
On research relating to social issues such as social responsibility, leadership, and peace from the Filipino perspective.
Includes bibliographical references.
In Tagalog.
Keywords: Responsibility -- Philippines; Leadership -- Philippines; Peace; Philippines -- Intellectual life